[(123)]FP-CIT SPECT scans initially rated as normal became abnormal over time in patients with probable dementia with Lewy bodies - van der Zande, J. J. (Eur J Nucl Med Mol Imaging, 2016)
PURPOSE: Decreased striatal dopamine transporter (DAT) binding on SPECT imaging is a strong biomarker for the diagnosis of dementia with Lewy bodies (DLB). There is still a lot of uncertainty about patients meeting the clinical criteria for probable DLB who have a normal DAT SPECT scan (DLB/S−). The aim of this study was to describe the clinical and imaging follow-up in these patients, and compare them to DLB patients with abnormal baseline scans (DLB/S+). METHODS: DLB patients who underwent DAT imaging ([(123)I]FP-CIT SPECT) were selected from the Amsterdam Dementia Cohort. All [(123)I]FP-CIT SPECT scans were evaluated independently by two nuclear medicine physicians and in patients with normal scans follow-up imaging was obtained. We matched DLB/S-− patients for age and disease duration to DLB/S+ patients and compared their clinical characteristics. RESULTS: Of 67 [(123)I]FP-CIT SPECT scans, 7 (10.4 %) were rated as normal. In five DLB/S− patients, a second [(123)I]FP-CIT SPECT was performed (after on average 1.5 years) and these scans were all abnormal. No significant differences in clinical characteristics were found at baseline. DLB/S− patients could be expected to have a better MMSE score after 1 year. CONCLUSION: This study was the first to investigate DLB patients with the initial [(123)I]FP-CIT SPECT scan rated as normal and subsequent scans during disease progression rated as abnormal. We hypothesize that DLB/S− scans could represent a relatively rare DLB subtype with possibly a different severity or spread of alpha-synuclein pathology (“neocortical predominant subtype”). In clinical practice, if an alternative diagnosis is not imminent in a DLB/S− patient, repeating [(123)I]FP-CIT SPECT should be considered.